2006
DOI: 10.1212/01.wnl.0000219565.32247.11
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase gene polymorphisms and sporadic ALS

Abstract: Frequent amino acid variants in the paraoxonase 1 and paraoxonase 2 genes are associated with sporadic ALS in a Polish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 30 publications
3
50
2
Order By: Relevance
“…Interestingly, recent studies have established that different functional PON polymorphisms are risk factors for different neurological diseases [22, 23]. It is possible that enhanced lipid peroxides target specific cells in different populations of patients; i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies have established that different functional PON polymorphisms are risk factors for different neurological diseases [22, 23]. It is possible that enhanced lipid peroxides target specific cells in different populations of patients; i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of sporadic ALS is thought to be multifactorial, with environmental, infectious and genetic etiologies. Reported associations with variants in diverse genes (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) have proven difficult to replicate. Advances in the technology for large-scale genotyping of single nucleotide polymorphisms (SNPs) have facilitated unbiased, genome-wide association studies.…”
mentioning
confidence: 99%
“…Because PON proteins reduce oxidation and are able to detoxify neurotoxins these proteins have been investigated for association with ALS. Polymorphisms in PON1 and PON2 as well as a haploblock spanning PON2 and PON3 were found to be associated with sALS (Saeed et al, 2006;Slowik et al, 2006). Since then several other studies in different populations have reported association of SNPs in the PON genes with sALS Landers et al, 2008;Morahan et al, 2007;.…”
Section: Paraoxonase Genes (Pon)mentioning
confidence: 96%